Frequency of glove puncture in the post mortem room. Issue 2 (February 1992) - Weston, J; Locker, G
Abstract : The post mortem room is a potential source of danger from contamination caused by glove punctures. The objective of this study was to assess the incidence of hand injury and hand contamination during post mortem examinations. A prospective study of injury and glove puncture rate was conducted during post mortem examinations performed in 1990 on adults in Northwick Park Hospital mortuary. Four pathologists and two assistants performed a total of 44 post mortem examinations on adults. All participants completed a questionnaire after each examination, recording the total number of gloves used and the number of hand injuries and glove perforations sustained. Just over 8.3% of gloves were punctured; 31.8% of these punctures went unnoticed. Evisceration was the procedure most likely to result in hand contamination. The study highlights a significant risk which could be reduced by more care, frequent glove changes, and hand washing during post mortem examinations. In particular, gloves should be changed and hand washed when evisceration has been completed.